Acute effects of cannabis consumption on exercise performance: a systematic and umbrella review - Charron, J.; Carey, V.; Marcotte-L'Heureux, V.; Roy, P.; Comtois, A. S.; Ferland, P. M. (The Journal of Sports Medicine and Physical Fitness, 2021)
INTRODUCTION: The goal of this systematic and umbrella review was to regroup all systematic reviews, non-systematic reviews and all original articles into one convenient publication that would facilitate the theoretical and applied scientific investigations directed on cannabis consumption and exercise performance, to update current findings on the matters, and assess evidence quality. EVIDENCE ACQUISITION: The systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) method. A computer-based systematic search was conducted in September 2019 through the Pubmed, Scopus and SPORTDiscus databases. The reliability of the systematic search was assured by having the article selection process entirely repeated by a second author. Strength of evidence of the selected articles was assesses using a modified version of the Downs and Black Checklist. EVIDENCE SYNTHESIS: The systematic search yielded a total of 8 peer-reviewed publications as well as 10 literature reviews. Results show that cannabis consumption prior to exercise induces decrements in performance (reduced ability to maintain effort, physical/maximal work capacity), undesired physiological responses (increased heart and breathing rate as well as myocardial oxygen demand) and neurological effects on balance (increased sway). CONCLUSIONS: Based on the articles included in this review, the authors conclude that cannabis consumption has an ergolytic effect on exercise performance and therefore does not act as a sport performance enhancing agent as raised by popular beliefs. Thus, cannabis consumption prior to exercise should be avoided in order to maximize performance in sports. Further research should mimic modern THC dosage (150 mg).